2013
DOI: 10.5604/17322693.1046538
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of Toll-like receptor signalling

Abstract: The mechanism of innate immunity is based on the pattern recognition receptors (PRR) that recognize molecular patterns associated with pathogens (PAMPs). Among PRR receptors Toll-like receptors (TLR) are distinguished. As a result of contact with pathogens, TLRs activate specific intracellular signaling pathways. It happens through proteins such as adaptor molecules, e.g. MyD88, TIRAP, TRIF, TRAM, and IPS-1, which participate in the cascade activation of kinases (IKK, MAP, RIP-1, TBK-1) as well as transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Toll interacting protein (TOLLIP) is an inhibitory adaptor protein, effectively inhibiting the activity of IRAK1 after TLR4 activation. Excess expression of TOLLIP has been shown to inhibit inflammation in response to TLR4 signaling (Antosz and Choroszynska, 2013). Interleukin-1 receptor-associated kinase 3 (IRAK3) restrains the dissociation of IRAK1 from Myd88 and the connections among TRAF6 complexes, causing interference of downstream signal relaying (van Hemert et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Toll interacting protein (TOLLIP) is an inhibitory adaptor protein, effectively inhibiting the activity of IRAK1 after TLR4 activation. Excess expression of TOLLIP has been shown to inhibit inflammation in response to TLR4 signaling (Antosz and Choroszynska, 2013). Interleukin-1 receptor-associated kinase 3 (IRAK3) restrains the dissociation of IRAK1 from Myd88 and the connections among TRAF6 complexes, causing interference of downstream signal relaying (van Hemert et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the number of T, B and dendritic cells significantly increase (22,23). As indicated by previous studies, TIPE2 may be involved in the regulation of multiple signalling transduction pathways (24,25). TIPE2 can inhibit the activation of c-jun N-terminal kinase (JNK) and p38 mitogen-activated protein kinase (MAPK), and decrease the activation of transcription factor activator protein-1, such that it negatively regulates the JNK and p38 MAPK signalling transduction pathways.…”
Section: Discussionmentioning
confidence: 64%
“…The anti inflammatory mechanism of statins is associated with NF-κB. Statins function to reduce the isoprenylation of Rho proteins, preventing Rho proteins from binding to the cell membrane, which decreases the release of NF-κB into the nucleus, thereby decreasing inflammatory cytokine secretion (24) and achieving an anti inflammatory response. Previous studies have found that statins can reduce the binding of bacterial LPS induced C Rel/p65 heterodimers with tissue factor κB sites, thereby regulating inflammatory factors at the gene level, promoting anti inflammatory cytokine (IL-10) synthesis and thereby playing a significant anti inflammatory role (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…They have an extracellular, transmembrane and cytoplasmic component. The extracellular region of the receptor is composed of leucine‐rich domains (LRR), while the cytoplasmic domain has a high homology to IL‐1R1, which is called the TIR domain (Toll‐IL‐1 receptor) . Toll‐like receptors occur mainly in the cell membrane (TLR1, TLR2, TLR4, TLR5, TLR6, TLR10, TLR11), but some are anchored in the membrane of cytoplasmic vesicles (TLR3, TLR7, TLR8 and TLR9) .…”
Section: Toll‐like Receptorsmentioning
confidence: 99%